Understanding Employee Turnover: Health, Safety, Work Environment, and Job Satisfaction Influence Commitment - Prakoso, Ananda; Budiono, Aris (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Puspose: This study examines the correlation of HSE and work environment on job satisfaction, with organizational commitment as a mediating factor. Methodology/Approach: In February 2025, a survey was conducted with 350 participants using the Krejcie and Morgan method. The survey aimed to assess the validity and reliability of the measurement instruments, test the hypotheses, and explore the relationships among the variables. The results indicated that Health, Safety, and Environment (HSE) practices significantly impacted organizational commitment. However, job satisfaction did not facilitate the relationship between HSE and organizational commitment. Results/Findings: Health, Safety, and Environment (HSE) practices significantly influence organizational commitment. The findings indicate that HSE initiatives create a safe and supportive work environment, which fosters employee trust, well-being, and loyalty. This, in turn, enhances their long-term commitment to the organization. While the work environment impacted job satisfaction, it did not significantly affect organizational commitment in this study. Additionally, job satisfaction was not identified as a meaningful mediator between other factors. This suggests that HSE practices and a supportive work environment have a stronger influence on organizational commitment than job satisfaction alone. Conclusions: HSE (Health, Safety, and Environment) practices significantly impact organizational commitment. In contrast, the work environment influences job satisfaction but does not directly affect commitment. Additionally, job satisfaction was not a significant mediator between these two constructs. Organizations should strengthen their HSE practices and create a safe, positive work environment to enhance employee engagement and organizational commitment. Initiatives such as leadership development, recognition programs, and growth opportunities can increase employee motivation and improve long-term performance.